Intellectual property rights and ASEAN development in the digital age - Chen, Lurong; Kimura, Fukunari 1958- (Routledge, Taylor & Francis Group, 2022)
"The trade-investment-service-intellectual property (IP) nexus remains at the heart of economic development and the main features of which are global value chains (GVCs) and digitalisation. The protection of intellectual property rights (IPR) has become a critical issue not only for advanced economies but also for emerging markets. This edited volume contributes to the debates on IPR protection and economic development from the perspective of Association of Southeast Asian Nations (ASEAN) member states. The book provides insights into the mechanism and evidence on how effective IPR protection will increase economic and social welfare via promoting innovation activities and providing incentives to diffuse knowledge and transfer technologies. Written by economists and lawyers from the region, these experts share their latest findings and thoughts on how countries in Southeast Asia have been progressively improving IPR protection and increasing the interoperability of different IPR regimes through regional cooperation to facilitate business operations in the context of digital transformation.
Literaturangaben und Index
Keywords: Technological innovations / Economic aspects / Southeast Asia; Intellectual property / Southeast Asia; Intellectual capital / Southeast Asia; Economic development / Southeast Asia; Economic development; Intellectual capital; Intellectual property; Technological innovations / Economic aspects; Southeast Asia